(untitled) (Colombia Medica, 2006)
Objective: To determine the prevalence of religious practice, family dysfunction and social support in older people with deppresive symptoms. Methods: A descriptive study was performed in La Selva Health Center (Cali, Colombia) during 2001. Measures used were depression (GDS-Yesavage Scale), intrinsic/extrinsic religiosity measurement (Gorsuch-McPherson), family APGAR (Smilkstein scale) and frequency of religious practice. Univariate and bivariate analyses were performed. Results: 136 subjects were recruited with an average age of 69.2±6.4 year old, 78 (57%) were male, 82 (60%) were married, 21 (15%) were widowers, 133 (97.8%) were believers or had religious practice; 90% were catholics, 126 (93%) of patients prayed at least once day, 60 (44.4%) had intrinsic religiosity, 46 (33.8%) extrinsic religiosity, and 16 (11.8%) mixed religiosity; 40 (29.4%) had family dysfunction, 69 (50.7%) had not an adequate social support; 10 (7.3%) had high depressive symptoms (GDS >5/15) and 5 (3.7%) had severe depressive symptoms (GDS >10/15). The presence of chronic diseases, and being a widower had more frequency in older people with deppresive symptoms (p< 0.05). Most old subjects with depression had no regular religious practice (p=0.03). Conclussion: Male gender, presence of chronic diseases and being a widower had more frequency in old people with deppresive symptoms (p< 0.05). Religious practice could be an important support for old patients’ health.